2018
DOI: 10.1111/bju.14521
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the frequency of Y‐chromosome microdeletions and the determination of a threshold sperm concentration for genetic testing in infertile men

Abstract: The prevalence of Y-chromosome microdeletions in infertile men appears to vary between populations and countries. A low sperm concentration was a predictive factor (P < 0.05) for identifying microdeletions in infertile males. A threshold for genetic testing of 0.5 million/mL would increase the specificity and lower the relative cost without adversely affecting the sensitivity. The rate of SSR was lower than that previously described in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 26 publications
2
25
0
1
Order By: Relevance
“…A high incidence of AZF deletions in Klinefelter patients had been reported in two small studies (Mitra et al ., ; Hadjkacem‐Loukil et al ., ), in contrast with other larger studies that have not found AZF deletions in this set of patients (Choe et al ., ; Simoni et al ., ; Rajpert‐De Meyts et al ., ; Johnson et al ., ). We just found 1 partial AZFc deletion in the Klinefelter syndrome subset which supports that there is no association between microdeletions and 47,XXY karyotype and the previous findings reporting a positive association are likely to be an occasional finding.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A high incidence of AZF deletions in Klinefelter patients had been reported in two small studies (Mitra et al ., ; Hadjkacem‐Loukil et al ., ), in contrast with other larger studies that have not found AZF deletions in this set of patients (Choe et al ., ; Simoni et al ., ; Rajpert‐De Meyts et al ., ; Johnson et al ., ). We just found 1 partial AZFc deletion in the Klinefelter syndrome subset which supports that there is no association between microdeletions and 47,XXY karyotype and the previous findings reporting a positive association are likely to be an occasional finding.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of Yq microdeletions in our population was 4.6% (4.0% if the analysis was limited to individuals with normal karyotype and 3.0% if only the complete AZF deletions were considered), which supports the values described in the literature (second cause for male infertility), with a global prevalence of 2–10% in infertile men (Hofherr et al ., ; Lo Giacco et al ., ; Tahmasbpour et al ., ; Wosnitzer, ; Mascarenhas et al ., ; Johnson et al ., ) and a lower frequency estimated in Europe (around 3%) (Colaco & Modi, ). Population variations seem to be responsible for the different values reported in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations